PENINGKATAN KREATIFITAS PEMBUATAN KEBUTUHAN PRIMER SABUN CUCI PIRING SECARA MANDIRI DI DAMA CATALIYA SUMBERSARI - Nafisah Isnawati (LPPM Universitas dr. Soebandi, 2025)
Soap is a surfactant used with water in the process of cleaning dirt. The use of soap is a daily necessity for cleaning the body and the surrounding environment, particularly for cleaning household items such as glassware and dishes. Dama Cataliya is a group of housewives in the Sumbersari Subdistrict, categorized as a community group with potential for empowerment to foster creativity and skills. The implementation method of the activity was carried out in the form of training and hands-on practice for making dishwashing liquid. The purpose of this activity was to enhance the skills and motivation of the Dama Cataliya group to become proficient and creative in producing dishwashing liquid that can be used daily.The outcomes of this activity include the community gaining knowledge about the ingredients, the process of making dishwashing liquid, and producing soap with good quality—sufficient foam, easy to rinse, and a distinctive lime fragrance. In conclusion, the implementation of this community service activity went smoothly and successfully. The participants were enthusiastic in attending the material presentation, discussions, and hands-on training sessions for making dishwashing liquid. They acquired valuable knowledge and increased creativity in independently producing high-quality dishwashing liquid.